2018
DOI: 10.1186/s12889-018-6257-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and symptoms of depression in different contexts – a cross-sectional study of Norwegian adolescents

Abstract: BackgroundThe purpose was to analyse the association between physical activity taking place in different contexts (sports club, gym, exercise independently and other organized physical activities) and symptoms of depression.MethodsThe study was based on self-reported cross-sectional data from the Ungdata survey, conducted in 2017 by the Norwegian Social Research (NOVA) institute in cooperation with regional centres for drug rehabilitation. The target group comprised 5531 15–16 years old adolescents (Grade 10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 31 publications
8
49
0
2
Order By: Relevance
“…Participation is voluntary with a single administration, which makes it difficult to know exactly how representative the data are, as some adolescents refused participation, whereas others consented but were absent at the time of data collection. The participation rate is similar to other published Ungdata studies (Kleppang, Hartz, Thurston, & Hagquist, 2018;Sandvik, Bakken, & Loland, 2018), as well as surveys in the field of EDs, such as Project EAT-III (Larson et al, 2011) and the Growing Up Today Study (Field et al, 1999), strengthening our confidence that these Note: Nonusers served as the reference category for the ORs. Snus frequency categories were defined as: nonusers ("never" or "have tried snus before, but do not use at all"), occasional users ("less often than once a week" or "every week but not daily"), and daily users ("every day" to examine other aspects of snus use, including flavors (e.g., bergamot, citrus, mint), amount, and duration.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Participation is voluntary with a single administration, which makes it difficult to know exactly how representative the data are, as some adolescents refused participation, whereas others consented but were absent at the time of data collection. The participation rate is similar to other published Ungdata studies (Kleppang, Hartz, Thurston, & Hagquist, 2018;Sandvik, Bakken, & Loland, 2018), as well as surveys in the field of EDs, such as Project EAT-III (Larson et al, 2011) and the Growing Up Today Study (Field et al, 1999), strengthening our confidence that these Note: Nonusers served as the reference category for the ORs. Snus frequency categories were defined as: nonusers ("never" or "have tried snus before, but do not use at all"), occasional users ("less often than once a week" or "every week but not daily"), and daily users ("every day" to examine other aspects of snus use, including flavors (e.g., bergamot, citrus, mint), amount, and duration.…”
Section: Discussionsupporting
confidence: 79%
“…The participation rate is similar to other published Ungdata studies (Kleppang, Hartz, Thurston, & Hagquist, 2018;Sandvik, Bakken, & Loland, 2018), as well as surveys in the field of EDs, such as Project EAT-III (Larson et al, 2011) and the Growing Up Today The cross-sectional design precludes any conclusions related to causality and the developmental trajectory of unhealthy eating and weight control practices in relation to snus onset.…”
Section: Discussionsupporting
confidence: 77%
“…Short formats of the HSCL (5-25 item scales) have been shown to perform almost as well as the full version [28]. Rasch analysis of the psychometric properties of the six-item HSCL scale used in the current study has previously shown that this scale works reasonably well [29]. Participants were asked if they had been affected by any of the following during the past week: "felt that everything is a struggle", "had sleep problems", "felt unhappy, sad or depressed", "felt hopelessness about the future", "felt stiff or tense", "worried too much about things".…”
Section: Methodsmentioning
confidence: 62%
“…Because Friday is the start of the weekend, this may particularly be a day of physical activity in the context of socializing. Some studies observed that physical activity in a club setting (sports club) or other organized activities are associated with lower depressive symptoms, opposed to exercising alone 44,18 . Further, leisure time physical activity, over non-leisure time, has been associated with lower odds of depression 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, leisure time physical activity, over non-leisure time, has been associated with lower odds of depression 45 . This suggests an important role of social physical activities: exercise that can be done in a social context such as in a group and physical activity that is perceived as enjoyable for mental health outcomes 46,44 . However, this explanation remains speculative, as we did not measure if participants engaged in social physical activities throughout the week or exercised alone.…”
Section: Discussionmentioning
confidence: 99%